Effect of different mechanical surface treatments on flexural strength of repaired denture base. - Hamid Neshandar Asli; Samiye Rahimabadi; Navid Belyani; Marzieh Neshandar Asli; Mehran Falahchai (Universidad de Concepción., 2022)
Aim: To assess the effect of different mechanical surface treatments on flexural strength of repaired denture base. Material and Methods: Sixty bar-shaped specimens of heat-polymerized acrylic resin were fabricated, and divided into six groups (n=10). All specimens, except the positive control group (group PC), were sectioned into halves to create a 1-mm clearance. A negative control group with no surface treatment (group NC) was also considered. Other groups underwent different surface treatments: group Laser; treated with erbium: yttrium-aluminum-garnet (Er:YAG) laser, group APA; airborne-particle abrasion (APA), group APA plus Laser; a combination of laser and APA, and group Bur; bur grinding. After measuring surface roughness (Ra) with a profilometer, all sectioned specimens were repaired by auto-polymerizing acrylic resin, and thermocycled afterward. Three-point bending test was performed by a universal testing machine. Data were statistically analyzed (α=0.05). Results: The mean surface roughness of all experimental groups were significantly higher than that of group NC (p<0.05). The mean flexural strength of all groups was significantly lower than that of group PC (p<0.05). Group B had significantly higher flexural strength than the other surface-treated groups (p<0.05). Group Laser had significantly higher flexural strength than groups APA (p=0.043) and APA plus Laser (p=0.023). No significant difference was found between groups APA and APA plus Laser (p=0.684). Conclusion: All surface treatments increased the surface roughness and flexural strength compared with the untreated group. The highest flexural strength was observed in specimens treated by bur grinding and then laser, however, it was still significantly lower than intact specimens.